Biomechanical study on fixation methods for horizontal oblique metacarpal shaft fractures - Yung-Cheng Chiu; Cheng-En Hsu; Tsung-Yu Ho; Yen-Nien Ting; Ming-Tzu Tsai; Jui-Ting Hsu (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Objective To investigate differences in the effectiveness of two lag screws, a regular bone plate, and locking bone plate fixation in treating horizontal oblique metacarpal shaft fractures. Materials and methods Horizontal oblique metacarpal shaft fractures were created in 21 artificial metacarpal bones and fixed using one of the three methods: (1) two lag screws, (2) a regular plate, and (3) a locking plate. All the specimens were subjected to the cantilever bending test performed using a material testing machine to enable recording of the force–displacement data of the specimens before failure. The Kruskal–Wallis test was used to compare failure force and stiffness values among the three fixation methods. Results The mean failure force of the two lag screw group (78.5 ± 6.6 N, mean + SD) was higher than those of the regular plate group (69.3 ± 17.6 N) and locking plate group (68.2 ± 14.2 N). However, the mean failure force did not significantly differ among the three groups. The mean stiffness value of the two lag screw group (17.8 ± 2.6 N/mm) was lower than those of the regular plate group (20.2 ± 10.5 N/mm) and locking plate group (21.8 ± 3.8 N/mm). However, the mean stiffness value did not significantly differ among the three groups. Conclusion The fixation strength of two lag screw fixation did not significantly differ from that of regular and locking bone plate fixation, as indicated by the measurement of the ability to sustain force and stiffness.